2010
DOI: 10.1038/onc.2010.464
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor β1 domains responsible for the antagonism with the ras oncogene: role of corepressors

Abstract: The thyroid hormone receptor (TR) is a suppressor of rasmediated responses. To characterize the receptor domains involved in this function, we analyzed a panel of TRb1 mutants for their ability to interfere with ras-driven cyclin D1 activation, formation of transformation foci and tumor growth in nude mice. Our results show that the domains and mechanisms responsible for the anti-transforming and anti-tumorigenic actions of the receptor are divergent from those operating in classical T3-dependent transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…NCoR induction appears to play a crucial role in the antitumorigenic and antimetastatic actions of the receptor (24), because these actions were reversed almost completely upon NCoR silencing. We also have shown that, in contrast with the native receptor, TRβ mutants unable to bind the corepressor cannot antagonize Ras-mediated transformation and tumorigenesis (26), reinforcing the idea that NCoR is an essential mediator of the tumor-suppressive actions of TRβ. TRβ-mediated up-regulation of NCoR could extend the scope of genes that are influenced by the receptor, because the corepressor has been shown to repress transcription through other nuclear receptors and numerous transcription factors with a role in cancer progression (1,12).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…NCoR induction appears to play a crucial role in the antitumorigenic and antimetastatic actions of the receptor (24), because these actions were reversed almost completely upon NCoR silencing. We also have shown that, in contrast with the native receptor, TRβ mutants unable to bind the corepressor cannot antagonize Ras-mediated transformation and tumorigenesis (26), reinforcing the idea that NCoR is an essential mediator of the tumor-suppressive actions of TRβ. TRβ-mediated up-regulation of NCoR could extend the scope of genes that are influenced by the receptor, because the corepressor has been shown to repress transcription through other nuclear receptors and numerous transcription factors with a role in cancer progression (1,12).…”
Section: Discussionmentioning
confidence: 76%
“…We have shown that this receptor retards tumor growth and suppresses invasion, extravasation, and metastasis formation in nude mice (23)(24)(25)(26). These tumor-suppressing effects are associated with a decreased expression of prometastatic genes (23).…”
mentioning
confidence: 99%
“…Mechanistically, we found that mutant receptors that are unable to recruit classical coactivators and to mediate T3-dependent transcriptional activation in transfection studies (35) still showed significant repression of TGF-β/SMAD transcriptional activity, although with less potency than the wild-type receptors. In addition, analysis of DBD mutants revealed that residues in this domain are required for repression of TGF-β-dependent transcription.…”
Section: Discussionmentioning
confidence: 94%
“…2 C and F). The mutations K288I and E457Q in ΤRβ and the equivalent mutation E401Q in TRα are located in the ligand-binding domain (LBD) and abolish the recruitment of coactivators and T3-dependent transcription, although they still bind T3 (35). However, these mutants maintain the ligand-independent activity and mediate significant T3-dependent repression of TGF-β-dependent transactivation, although with less potency than the WT receptors.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation